Severe spontaneous vertebral fractures after denosumab discontinuation: three case reports. Issue 5 (May 2016) - Aubry-Rozier, B.; Gonzalez-Rodriguez, E.; Stoll, D.; Lamy, O.
Abstract Osteoporosis treatments are usually given for a limited period of time in order to balance benefits and risks. We report three cases of postmenopausal women without any previous fragility fracture who presented severe spontaneous vertebral fractures after denosumab discontinuation. We think that the occurrence of these fractures could be explained by the severe rebound effect observed after denosumab discontinuation and that a consensus regarding the end of treatment with denosumab has to be defined.